The effects of genetic inheritance E-game to undergraduate students - Farah Wahida Ibrahim; Asmah Hamid; Mazlyzam Abdul Latif; Soon Singh Bikar Singh; Nor Fadilah Rajab; Nurul Farhana Jufri (Penerbit Universiti Kebangsaan Malaysia, 2022)
The COVID-19 outbreak that is occurring worldwide has affected the education system, as the closure of education institutions has halted teaching and learning activities. Nevertheless, online education is being widely applied to complete the curriculum. As learning activities are limited by the prohibition of face-to-face classes, an E-game on genetic disease inheritance was designed and introduced to undergraduate Biomedical Science students of Universiti Kebangsaan Malaysia (UKM). In this approach, the students were divided into small groups of 5-7 students and they were required to grasp the basic knowledge of genetic disease inheritance including drawing a pedigree tree in order to understand genetic-based diseases, develop three case studies, four case studies-related questions and also provide the answer scheme beforehand. During the E-game, the Microsoft Teams online learning platform was used. Each of the groups took turns to present case studies on the topic of genetic disease inheritance and answered questions. Marks were given for each of the answers. The students’ feedback was collected to evaluate the outcome of this approach. Their understanding on pedigree drawing topics, ability to draw pedigree diagram and analysing genetic inheritance case studies were significantly (p<0.001) increased after the e-game implementation. In addition, the e-game helped them to develop several skills such as teamwork and strategizing. Overall, the students were benefited with the approach, even though some limitations in internet accessibility and devices problems were encountered during the e-game. As conclusion, the e-game was successfully tailored to deliver the genetic inheritance topic previously outlined for face to face session.